In vitro transfection of anti-tumor miR-101 induces BIM, a pro-apoptotic protein, expression in acute myeloid leukemia (AML) - Nikoonahad Lotfabadi, Narges; Mohseni Kouchesfahani, Homa; Sheikhha, Mohammad Hasan; Kalantar, Seyed Mehdi (Technische Universität Dortmund, 2017)
Acute myeloid leukemia (AML) frequently relapses after initial treatment, though it is possible that drug resistance occurs. Hence, it seems necessary to develop novel therapies such as gene therapy specifically via miRNA trans- fection. MicroRNA-101 has been considered as a tumor suppressor in different types of cancer. It is demonstrated that exogenous miR-101 transfection is associated with decreased viability in AML in this paper. Besides, the increase of pro-apoptotic protein BIM expression in both mRNA and protein level has been illustrated. The recent findings provide an insight into the novel function of miR-101 in AML by activating BIM as an important mediator in intrinsic apoptosis pathways. Generally, miR-101 has been considered as a therapeutic target in our data and might have a valuable role in AML.
EXCLI Journal;Vol. 16 2017
Keywords: AML; miR-101; BIM; Apoptosis; 610